Stagnation Point Flow towards a Melting Shrinking Sheet in an Upper Convected Maxwell Fluid - Lok, Yian Yian; Abdul Karim, Mohamad Faisal; Pop, Ioan (American Institute of Physics, 2013)
An analysis of the steady stagnation point flow towards a melting shrinking sheet in an upper convected Maxwell (UCM) fluid has been studied. A similarity transformation is used to reduce the governing partial differential equations to third-order nonlinear ordinary differential equation which are then solved numerically using an implicit finite difference method, namely the Keller-box method. The influences of the melting and shrinking parameters on the flow and beat transfer characteristics are studied. Representative results for the reduced skin friction coefficient and the reduced heat flux from the surface of sheet (local Nusselt number) as well as the velocity and temperature profiles are presented. 1t is found that the solutions are non-unique for some values of the shrinking parameter.